Impact of stoma leakage in everyday life: data from the Ostomy Life Study 2019. (24th March 2022) - Jeppesen, Palle Bekker; Vestergaard, Martin; Boisen, Esben Bo; Ajslev, Teresa Adeltoft
Abstract : Background: Many people with a stoma experience leakage of stomal effluent. Aim: To investigate the impact of leakage on individuals with a stoma. Methods: The Ostomy Life Study 2019 included a survey concerning experiences with stomal effluent leakage and the validated Ostomy Leak Impact tool. Findings: Respondents with frequent leakage episodes were significantly more affected emotionally and they were feeling less in control than those who rarely or never experienced leakage. The emotional impact of experiencing leakage onto clothes appeared to last up to 1 year after the last leakage incidence. Because of worrying about leakage users increased their product usage and, of those who were in employment, 65% reported that leakage and the related worry influenced their ability to work. Conclusion: Most people with a stoma were emotionally impacted by experiencing leakage, especially by leakage outside the baseplate (resulting in soiled clothes). New solutions are warranted that can help reduce the impact of leakage.